2020
DOI: 10.1093/nar/gkaa513
|View full text |Cite
|
Sign up to set email alerts
|

Human OAS1 activation is highly dependent on both RNA sequence and context of activating RNA motifs

Abstract: 2′-5′-Oligoadenylate synthetases (OAS) are innate immune sensors of cytosolic double-stranded RNA (dsRNA) and play a critical role in limiting viral infection. dsRNA binding induces allosteric structural changes in OAS1 that reorganize its catalytic center to promote synthesis of 2′-5′-oligoadenylate and thus activation of endoribonuclease L. Specific RNA sequences and structural motifs can also enhance activation of OAS1 through currently undefined mechanisms. To better understand these drivers of OAS activat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
34
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 30 publications
(38 citation statements)
references
References 60 publications
2
34
0
Order By: Relevance
“…OAS1 is an oligoadenylate synthetase enzyme that binds dsRNA and changes conformation to generate oligoadenylates and activate RNase L to digest RNA. 92,93 It has also been proposed that OAS1 may have RNase-independent roles. 29,30 OAS1 is expressed by multiple cell types in the myeloid lineage including monocytes, macrophages, and microglia, as well as natural killer cell lymphocytes.…”
Section: Discussionmentioning
confidence: 99%
“…OAS1 is an oligoadenylate synthetase enzyme that binds dsRNA and changes conformation to generate oligoadenylates and activate RNase L to digest RNA. 92,93 It has also been proposed that OAS1 may have RNase-independent roles. 29,30 OAS1 is expressed by multiple cell types in the myeloid lineage including monocytes, macrophages, and microglia, as well as natural killer cell lymphocytes.…”
Section: Discussionmentioning
confidence: 99%
“…The data presented here provide support for OAS1 linking AD and critical illness with COVID-19 by controlling the pro-inflammatory output of myeloid cells. OAS1 is an oligoadenylate synthetase enzyme that binds dsRNA and changes conformation to generate oligoadenylates and activate RNase L to digest RNA (Schwartz and Conn, 2019;Schwartz et al, 2020). It has also been proposed that OAS1 may also have RNase-independent roles (Kristiansen et al, 2010;Li et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…OAS1 is a member of OAS family which acts as antiviral enzymes induced by interferon. It was reported that neutrophils, which contribute to tumor metastasis through multiple pathways, were the top tumor immune infiltrating cell type associated with OAS in in breast cancer [ 35 ]. CDH1 deletions have been shown to cause cancers with immune cell infiltration, activation of targetable immune checkpoint pathways and gene expression related to T-regulatory (Treg) cell signaling [ 36 ].…”
Section: Discussionmentioning
confidence: 99%